The Effect of Replacing Fish Flour with Processed Shrimp Waste Flour Through Various Processes on Performance Broiler - Bayu Gilang Perkasa; Mairizal Mairizal; Noverdiman Noverdiman (Fakultas Peternakan Universitas Jambi, 2022)
This study aims to determine the ability of shrimp waste processing with several combinations of processing such as soaking using husk ash water filtrate, steaming and fermentation using the Trichoderma viridae fungus, as well as to determine the optimal level and level of using processed shrimp flour to replace fish meal in broiler chicken rations. . The study was conducted experimentally using a completely randomized design method consisting of 5 treatments and 4 replications. The treatment given was replacing fish meal with processed shrimp waste flour which consisted of P0 = 0% processed shrimp waste flour, P1 = 25% processed shrimp waste flour, P2 = 50% processed shrimp waste flour, P3 = 75% processed shrimp waste flour. and R4 100% processed shrimp waste flour. The data obtained were tabulated using the Microsoft Excel program, then analyzed using analysis of variance (ANOVA), if there were differences, then the Multiple Distance Test (Duncan's). The observed variables consisted of changes in the nutritional content of shrimp waste before and after processing, feed consumption, body weight gain and feed conversion in broiler chickens. The results of this study indicate a decrease in the nutritional content of processed shrimp waste. The replacement of fish meal with processed shrimp waste in broiler chicken rations had a very significant effect (P<0.01) on consumption and body weight gain, but had no effect (P>0.05) on feed conversion value. Based on the results of the study, it can be concluded that the processing of shrimp waste through several processes has not been able to improve the nutritional content of shrimp waste. The use of processed shrimp waste flour can be used up to 50% level as a substitute for fish meal in broiler chicken rations. Suggestions that can be given are the length of processing time from shrimp waste can be reduced in order to minimize factors that can damage or reduce the nutrition of shrimp waste. Keywords: Shrimp Waste, Trichoderma viride, Fermentation, Broiler, Performance